Graphene coated piezo-resistive fabrics for liquid composite molding process monitoring. (18th August 2017) - Ali, Muhammad A.; Umer, Rehan; Khan, Kamran A.; Samad, Yarjan A.; Liao, Kin; Cantwell, Wesley
Abstract: In this study, the graphene coated piezo-resistive fabrics have been exploited for liquid composite molding process monitoring. The utility of this novel technique has been demonstrated through compaction and flow monitoring experiments. The coated fabrics are subjected to a series of compaction tests to monitor resistance changes during the compaction cycle. During mechanical compression, the change in resistance has been found to be inversely proportional to the strain associated with the applied load. The repeatability of the change in the electrical resistance is confirmed via a series of vacuum assisted, stepwise and cyclic compression tests. The overall sensitivity of around 30% change in resistance is observed. The results highlight very small differences between the wet and dry compaction cycles when using silicone oil as the test fluid, suggesting that a nonconductive fluid offers negligible interference in the graphene coatings. The fabrics are subsequently used in a full resin infusion cycle to monitor the resistance change during the filling and post-filling stages. A continuous change in the resistance of the fabric is observed during, and after resin infusion process, highlighting the applicability of this novel technique for full process monitoring during the compaction and resin flow stages, in addition to cure monitoring.